Living and surviving the Paraguay-Brazil border: market, nationality and workers - Lima, Cíntia Fiorotti (Revista de Ciências Sociais, 2018)
Commercial growth in Salto Del Guairá / PY has increased the number of Brazilian workers who have daily moved from Guaíra / PR and Mundo Novo / MS to work as vendors in stores in the neighboring country, as well as in other activities transport and marketing of goods at this border. In this study we seek to analyze the contradictions and conflicts surrounding work and the market in Salto del Guairá, problematizing some of the difficulties faced by local workers and by other individuals who seek in these places ways of survival. The study seeks to analyze the differences between the border sought by a portion of the local dominant class and that experienced by the workers.To do so, we use oral sources with owners of stores and vendors and the analysis of material published in the local newspaper Rio Paranazão.